Guangdong Telecom Corporation --A Case Study Of Reinforce Strategic Cost Management And Search For The Way Of Innovation - Wang, Ana (2008)
This thesis points out that the company should change their key emphasis from production cost control to the overall value chain control to realize a strategic vision and solve the cost problems.